Antarease-like Zn-metalloproteases are ubiquitous in the venom of different scorpion genera - Ortiz, Ernesto; Rendón-Anaya, Martha; Rego, Solange Cristina; Schwartz, Elisabeth Ferroni; Possani, Lourival Domingos (Biochimica et biophysica acta, 2014)
The venoms of several scorpion species have long been associated with pancreatitis in animal models and humans. Antarease, a Zn-metalloprotease from Tityus serrulatus, is able to penetrate intact pancreatic tissue and disrupts the normal vesicular traffic necessary for secretion, so it could play a relevant role in the onset of acute pancreatitis. The cDNA libraries from five different scorpion species were screened for antarease homologs with specific primers. The amplified PCR products were cloned and sequenced. A structural model was constructed to assess the functionality of the putative metalloproteases. A phylogenetic analysis was performed to identify clustering patterns of these venom components. Antarease-like sequences were amplified from all the screened cDNA libraries. The complete sequence of the antarease from T. serrulatus was obtained. The structural model of the putative antarease from Tityus trivittatus shows that it may adopt a catalytically active conformation, sharing relevant structural elements with previously reported metalloproteases of the ADAM family. The phylogenetic analysis reveals that the reported sequences cluster in groups that correlate with the geographical localization of the respective species. Antareases are ubiquitous to a broad range of scorpion species, where they could be catalytically active enzymes. These molecules can be used to describe the evolution of scorpion venoms under different ecogeographic constrains. For the first time the complete sequence of the antareases is reported. It is demonstrated that antareases are common in the venom of different scorpion species. They are now proposed as targets for antivenom therapies.